Red blood cell distribution width and all-cause mortality in congestive heart failure patients: a retrospective cohort study based on the Mimic-III database - Ji, Xuan; Ke, Weiqi (Frontiers in Cardiovascular Medicine, 2023)
BACKGROUND: The red blood cell distribution width (RDW) is a metric that measures the variation in the size of red blood cells and is presented as the red blood cell volume coefficient of variation. Increased RDW levels are closely linked to an elevated risk of death from congestive heart failure (CHF) and might be a new risk marker for cardiovascular disease. This research sought to evaluate the possible link between RDW levels and all-cause mortality in CHF patients after controlling for other covariates. METHODS: The publicly accessible Mimic-III database served as the source of data for our research. We employed ICU admission scoring systems to gather information on each patient's demographical data, laboratory test results, comorbid conditions, vital signs, and scores. Among CHF patients, the link between baseline RDW levels and short-, medium-, and long-term all-cause mortality was evaluated by Cox proportional hazard analysis, smooth curve fitting, and Kaplan–Meier survival curves. RESULTS: In total, 4955 participants were selected for the study with an average age of 72.3±13.5 years (old) and with males accounting for 53.1%. The findings recorded from the fully adjusted Cox proportional hazard model showed that higher RDW was linked to a greater risk of 30-day, 90-day, 365-day, and 4-year all-cause death; the HRs and 95% confidence intervals were 1.11 (1.05, 1.16), 1.09 (1.04, 1.13), 1.10 (1.06, 1.14), and 1.10 (1.06, 1.13), respectively. The results were stable and reliable using subgroup analysis. Smooth curve fitting and the K-M survival curve method further validated our results. CONCLUSION: The RDW levels had a u-shaped connection with 30-day mortality. The RDW level was linked to an elevated risk of short-, medium-, and long-term all-cause death among CHF patients. KEYWORDS: Congestive heart failure; Red blood cell distribution width; all-cause mortality; Cox proportional hazards regression